The Contribution of Custom Institutions in Implementing Custom Sanctions in Gorontalo - Fence M Wantu; Dian Ekawaty Ismail; Nuvazria Achir (IAIN Manado, 2022)
Efforts to optimize existing customary institutions in the province of Gorontalo in law enforcement during society are significant. The organization of customary institutions needs to be addressed and arranged so that they can be enjoyed and utilized. This study uses a sociological juridical approach by obtaining data by interviewing figures from the Gorontalo traditional institutions. This research carries out by analysis through reduction, presentation of data, and conclusion?Gorontalo customary institution. The study results show that the position of traditional institutions in Gorontalo Province is one of the guidelines for people's lives. Customary institutions are the tools that are used and considered to be able to maintain the values of customary law itself. Imposing sanctions through traditional institutions is more effective because an adat institution grows based on values that live in society and recognize and adhered to for generations. In addition, customary institutions help prevent the accumulation of cases in court. The maximum of this research lies in the space given by the government to customary institutions both in ceremonial activities such as marriages and in law enforcement processes. In addition, community participation needs to maintain and utilize the presence of this traditional institution.